Government revenue and spending nexus in regional Indonesia: Causality approach - Ratu Eva Febriani; Roosemarina Anggraini Rambe (Economics, Management and Sustainability)
This study aims to test the hypothesis that explains the relationship between tax revenue and government spending in six Indonesian regions. Furthermore, the units of analysis were districts and cities in each region from 2006 to 2017, and a Granger panel causality approach was used. The results showed five experienced bidirectional causalities between tax revenues and local government spending out of the six regions, namely Java, Sumatra, Kalimantan, Sulawesi, and the Bali & Nusa Tenggara. Also, there was fiscal synchronisation in five regions, while the tax-spend hypothesis applies in the Papua & Maluku regions. Therefore, the local governments in these regions need to be careful in deciding actions related to increasing revenue. This can be achieved through the tax sector's optimisation and expenditure increment by encouraging public spending from the administration.